Technology-assisted problem solving for engineering education interactive multimedia applications - Sidhu, Manjit Singh, 1971- (Engineering Science Reference, 2010)
"This book explores best practices in assisting students in understanding engineering concepts through interactive and virtual environments"--Provided by publisher.